1974
DOI: 10.1515/bchm2.1974.355.1.669
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hypophysectomy, Thyroid Hormone and Insulin on the Activity of 3-Hydroxy-3-methylglutaryl-Coenzyme A Reductase in Rat Liver

Abstract: 1) Hypophysectomy abolishes the diurnal rhythm of hepatic hydroxymethylglutarylCoA reductase activity in rats.2) A single dose of triiodothyronine applied to hypophysectomized rats restored the activity of the enzyme to the high control levels of sham-operated animals within 48 hours, but failed to do so within 6 hours.3) Injection of insulin into hypophysectomized rats failed to increase the low reductase activities. 4) The interrelationship of thyroid hormone and insulin in the regulation of hepatic choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1976
1976
1985
1985

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Thus Lakshmanan et al (1973) demonstrated that administration of insulin to normal or diabetic rats resulted in an increase in hepatic reductase activity and rate of cholesterogenesis even if the treatment was performed in the middle of the light period and in animals that did not have access to food. Similarly it has been established that streptozotocin-induced diabetes in rats results in a marked decrease in the total activity of HMG-CoA reductase in the liver (Huber et al, 1973;Lakshmanan et al, 1973;Uchida et al, 1979;Young et al, 1982). However, relatively few studies have attempted to study the possible role of insulin in modulating the fraction of HMG-CoA reductase in the active form, i.e.…”
mentioning
confidence: 83%
“…Thus Lakshmanan et al (1973) demonstrated that administration of insulin to normal or diabetic rats resulted in an increase in hepatic reductase activity and rate of cholesterogenesis even if the treatment was performed in the middle of the light period and in animals that did not have access to food. Similarly it has been established that streptozotocin-induced diabetes in rats results in a marked decrease in the total activity of HMG-CoA reductase in the liver (Huber et al, 1973;Lakshmanan et al, 1973;Uchida et al, 1979;Young et al, 1982). However, relatively few studies have attempted to study the possible role of insulin in modulating the fraction of HMG-CoA reductase in the active form, i.e.…”
mentioning
confidence: 83%
“…An increase was observed after injection of pharmacological doses of insulin (Nepokroeff et al, 1974), glucagon (Huber et al, 1973) or tri-iodothyronine (Ness et al, 1973). In experiments with rat liver slices, Bortz (1968) found that injection of noradrenaline resulted in a twofold stimulation of cholesterol biogenesis from [1-14C]acetate, with a lag period of 12h.…”
mentioning
confidence: 99%